The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.29333/ejmste/13057
|View full text |Cite
|
Sign up to set email alerts
|

Peer assessment processes in a problem-solving activity with future teachers

Abstract: Assessing problem-solving remains a challenge for both teachers and researchers. With the aim of contributing to the understanding of this complex process, this paper presents an exploratory study of peer assessment in mathematical problem-solving activities. The research was conducted with a group of future Secondary mathematics teachers who first were asked to individually solve an open-ended problem and then, to assess a classmate’s answer in pairs. We present a study of two cases involving two pairs of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…The peer assessments assigned at random to the assessors are shown in Table 2. We applied three categories of analysis to systematize this study: general process, representations used, and solutions found (de- Armas-González et al, 2023). To address the research questions with in-depth discussions, we collected data using various methods, such as a survey, an interview, phone calls, and informal discussions.…”
Section: Methodsmentioning
confidence: 99%
“…The peer assessments assigned at random to the assessors are shown in Table 2. We applied three categories of analysis to systematize this study: general process, representations used, and solutions found (de- Armas-González et al, 2023). To address the research questions with in-depth discussions, we collected data using various methods, such as a survey, an interview, phone calls, and informal discussions.…”
Section: Methodsmentioning
confidence: 99%
“…Other findings admit that academic programs at this type of university are designed to break down traditional disciplinary boundaries, encouraging students to engage in problem-solving activities (de- Armas-González et al, 2023). The special attention must be paid towards learning through practical, real-world experience to form professional competence as well as readiness to innovation, creativity, and problem-solving (Kong, 2021).).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, the recent findings demonstrate that the university of future must possess certain characteristics. These characteristics refer to hybrid model of learning (Gadhoum, 2022), sustainability and inclusivity (Moral & Villarente 2024), interdisciplinary curriculum (de- Armas-González et al, 2023), and practice-based learning (Kong, 2021).…”
Section: Project-based Learningmentioning
confidence: 99%
“…Table 3 demonstrates the most essential future evaluation methods according to teachers. Teachers must co-design assessment and evaluation systems through collective bargaining [46,50]. Learning data should not be the only or primary source of teacher performance data.…”
Section: Future Teachers' Assessmentmentioning
confidence: 99%